Comparative Functional Outcomes After Corneal Crosslinking Using Standard, Accelerated, and Accelerated With Higher Total Fluence Protocols. Issue 4 (April 2019) - Lang, Paul Z.; Hafezi, Nikki L.; Khandelwal, Sumitra S.; Torres-Netto, Emilio A.; Hafezi, Farhad; Randleman, J. Bradley
Abstract : Purpose: To compare the relative 12-month corneal crosslinking (CXL) functional outcomes using standard protocol and accelerated protocols in patients with progressive keratoconus. Methods: CXL was performed using 3 epithelium-off protocols: standard [3 mW/cm 2 for 30 minutes, 5.4 J/cm 2 (S3/30 -CXL)], accelerated with equivalent total irradiance [9 mW/cm 2 for 10 minutes, 5.4 J/cm 2 (A9/10 -CXL)], and accelerated with increased total irradiance [30 mW/cm 2 for 4 minutes, 7.2 J/cm 2 (A30/4 -CXL)]. Efficacy measurements were evaluated 12 months after treatment with Scheimpflug imaging (Pentacam HR) and included change in maximum keratometry (K Max), corrected distance visual acuity (CDVA), other keratometric variables, pachymetry, keratoconus indices, astigmatism, asphericity, manifest refraction, and higher order aberrations. Results: Ninety-three eyes (67 patients) were evaluated: 35 eyes (26 patients) with S3/30 -CXL, 29 eyes (19 patients) with A9/10 -CXL, and 29 eyes (22 patients) with A30/4 -CXL. Mean [INCREMENT]K Max was −1.53 ± 2.1 diopter (D) for S3/30 -CXL, −0.71 ± 1.3 D for A9/10 -CXL, and −0.70 ± 2.3 D for A30/4 -CXL ( P = 0.37). Mean [INCREMENT]CDVA(logMAR) was −0.18 ± 0.2 for S3/30 -CXL, −0.13 ± 0.2 for A9/10 -CXL, and −0.18 ± 0.2 for A30/4 -CXL ( P = 0.79). [INCREMENT]K Mean (r = −0.29 to −0.46), anterior asphericity (r = −0.34 to −0.40), and central keratoconus index (r = −0.18 to −0.38) best correlated with [INCREMENT]CDVA. S3/30 -CXL had greater changes in index of surface variance, index of vertical asymmetry, keratoconus index, and regularization index compared to A9/10 -CXL and A30/4 -CXL. There were no other differences between protocols. Conclusions: All 3 protocols showed improvements in K Max, CDVA, and other variables, with similar functional outcomes for each despite greater change in keratoconus indices after S3/30 -CXL. Correlations between change in measured variables and CDVA were poor overall; however, K Mean, central keratoconus index, and anterior asphericity were better correlated with CDVA than K Max.